1986
DOI: 10.1007/bf02374354
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization losses from prilled urea, urea supergranules (USG) and coated USG in rice fields

Abstract: Summary About 8.4 per cent of applied nitrogen was lost as ammonia during a week after application when prilled urea was broadcast or banded and incorporated in soil 20 days after sowing of rice. Ammonia volatilization was reduced to 3.3 per cent when urea supergranules (USG) were used. Coating of USG with DCD or neem cake showed no advantage. Ammonia volatilization was only 0.7 to 1.6 per cent when fertilizer was applied at panicle initiation stage of rice; highest values were again obtained with prilled urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This suggests that the obviously lower NH 3 volatilization after the second topdress in W23 and Z11 was probably due to larger leaf area of these cultivars. It has been reported that more sunlight intensity could cause larger amount of NH 3 volatilization (Sudhakara and Prasad, 1986;Tian et al, 2001). Therefore, larger leaf area could block more sunlight to paddy water and then lead to less NH 3 volatilization.…”
Section: High-nue Rice Cultivars Reducing N Losses From Paddy Fieldsmentioning
confidence: 99%
“…This suggests that the obviously lower NH 3 volatilization after the second topdress in W23 and Z11 was probably due to larger leaf area of these cultivars. It has been reported that more sunlight intensity could cause larger amount of NH 3 volatilization (Sudhakara and Prasad, 1986;Tian et al, 2001). Therefore, larger leaf area could block more sunlight to paddy water and then lead to less NH 3 volatilization.…”
Section: High-nue Rice Cultivars Reducing N Losses From Paddy Fieldsmentioning
confidence: 99%
“…Another method to improve the NUE is the use of urea super granules (USG), invented by the International Fertilizer Development Center . Several studies have shown that the use of USGs can not only reduce the ammonia volatilization losses but also reduce the usage of fertilizer in the fields compared to the traditional fertilizer. , However, USG without coating must be placed deeply to avoid the burn of seeds or plant roots and ammonia volatilization by fast dissolving in paddy soil. The deep placement method of the USG is labor-intensive and time-consuming, which has limited it use in large-scale agricultural production systems .…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have shown that the use of USGs can not only reduce the ammonia volatilization losses but also reduce the usage of fertilizer in the fields compared to the traditional fertilizer. 10,11 However, USG without coating must be placed deeply to avoid the burn of seeds or plant roots and ammonia volatilization by fast dissolving in paddy soil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, after 1, 2 and 3 weeks of incubation total mineral-N in soil was significantly more under field capacity moisture than under submergence. This will be expected due to higher loss of N due to ammonia volatilization (Sudhakara and Prasad, 1986;Simpson et al, 1988;Reddy et al, 1990;Prasad et al, 1999) and denitrification (Mosier and Hutchinson, 1981;John et al, 1989;Eichner, 1990;Aulakh et al, 1992) under submerged conditions. The results of the present study thus show that under aerobic conditions as obtained under field capacity moisture DCD is an effective nitrification inhibitor but it may not be so under submerged conditions.…”
Section: Total Mineral-nmentioning
confidence: 96%
“…The evils of over-fertilization with nitrogen include nitrate pollution of groundwater (Muir et al, 1973;Duynisveld et al, 1988;Power and Schepers, 1989;Addiscott et al, 1996;Owens et al, 1992;Spalding and Exner, 1993;Nolan et al, 1997;Powlson, 1997), increased nitrate concentration in vegetables (Brown and Smith, 1966), emission of ammonia to the atmosphere (Sudhakara and Prasad, 1986;Simpson et al, 1988;Reddy et al, 1990;Kirchmann et al, 1998;Prasad et al, 1999) which adds to the acid rain (Whelpdale et al, 1997) and emission of N 2 O to the atmosphere (Freney et al, 1978;Mosier and Hutchinson, 1981;John et al, 1989;Eichner, 1990;Aulakh et al, 1992) which depletes the ozone layer (Grobecker et al, 1975) and contributes to the global warming (Yung et al, 1976;Rhode, 1990). These harmful effects of over-fertilization with nitrogen can be partly mitigated with the use of nitrification inhibitors (Sommer and Mertz, 1974;Rodgers, 1986;Owens, 1987;Owens et al, 1992;Prasad and Power, 1995).…”
Section: Introductionmentioning
confidence: 98%